CHANGES IN THE DEVELOPMENT TRENDS OF ORGANIC FARMING IN THE WORLD - Barbara Gołębiewska; Tomasz Pajewski (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2025)
Despite growing consumer interest, the supply of organic products in many countries has not kept pace with increasing demand. This is occurring alongside significant changes in the number of organic farms, the area they occupy, and their production volumes. This study provides fundamental insights into organic agriculture within the European Union and globally. The objective was to assess the current state and development trends in organic farming, with a particular focus on EU countries. The analysis considered fully organic farms – those in which the entire utilized agricultural area (UAA) and/or the entire livestock population has been converted or is in the process of being converted to organic practices. The study utilized data from reports by FiBL, FADN, and FAO on organic agriculture for the period 2012–2022. Findings indicate that, over the past decade, organic farming has exhibited a strong upward growth trend worldwide. Additionally, many countries have experienced a significant rise in organic food consumption, driven by increasing consumer awareness of food quality. While organic farming and the organic food industry present viable solutions for environmental protection, the current production system may not be universally applicable to all countries in its present form.